An evaluation of the role of eggs and DATEM on the quality of gluten-free sorghum bread - Bize, Magali (Kansas State University, 2012)
Due to an increase in awareness of celiac disease, the gluten-free market continues to expand. However, gluten-free breads are still characterized by a poor structure and overall mediocre quality. This research was aimed at determining the impact of egg addition as well as an antistaling agent (DATEM) on the quality of a batter-based gluten-free sorghum bread. Gluten-free bread loaves containing 20, 25, or 30% eggs (as is) on a flour basis were evaluated against a control (no egg). The impact of the antistaling agent, DATEM at 0.5% was also studied for each of these formulations. Quality factors evaluated included water activity, color, specific volume, and cell size. Texture profile analysis was performed to evaluate staling rate based on changes in crumb hardness values and a trained panel evaluated staling attributes by descriptive analysis. Finally, a consumer acceptance test on sorghum bread with and without eggs was also conducted. Results showed that sorghum breads with eggs had higher specific volumes than control (increase from 0.06 cm[superscript]3/g to 0.11 cm[superscript]3/g), while DATEM had a negative effect on the volume of gluten-free bread (decrease of 0.73 cm[superscript]3/g). Eggs also improved cell structure and produced significantly darker crust (p<0.05). Additionally, the addition of eggs reduced bread hardness (from 54 g force to 142 g force on fresh bread) and slowed the rate of staling over the 12 day storage period studied. Descriptive analysis results confirmed the findings of the texture analysis, showing control bread significantly harder (p<0.05) than egg-containing bread at days 0 and 4. The consumer test indicated a significant preference (p<0.05) for sorghum bread with eggs over the control. The overall acceptability score for this bread was above 6 on a 1 to 9 hedonic scale. The score was closer to 7 when the bread was rated by consumers with celiac disease. This research proved that the addition of eggs to a gluten-free sorghum bread formulation resulted in delayed staling and better overall quality and acceptability of the product.
Keywords: Gluten-free bread; DATEM; Eggs; Staling; Quality; Food Science (0359)